Pengembangan E-Modul Biologi Berbasis Inklusi Terintegrasi Profil Pelajar Pancasila - Tilal Afian; Sahratullah (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to develop an inclusion-based biology e-module integrated with Pancasila student profiles. The method used in developing this e-module refers to the ADDIE model, which consists of 5 main stages, namely: Analyze, at this stage, the research team collects data related to learning problems; Design, at this stage, the activities of preparing learning tools, preparing assessment instruments, and preparing the initial draft of an inclusion-based e-module integrated with Pancasila student profiles. Development, at this stage, develops an inclusion-based biology e-module, validates the module and tests the readability of the module by subject teachers. Data from validation results of the Biology E-Module that has been developed obtained a total score from expert validator I of 68.67% and an expert validator II score of 73.67%. The conclusions obtained in developing an inclusion-based biology e-module integrated with the Pancasila student profile are valid and can be used as a learning medium for inclusive students.